Short-term effectiveness and side effects of ketogenic diet for drug-resistant epilepsy in children with genetic epilepsy syndromes - Muthaffar, Osama Y.; Alyazidi, Anas S.; Alsowat, Daad; Alasiri, Abdulaziz A.; Albaradie, Raidah; Jad, Lamyaa A.; Kayyali, Husam; Jan, Mohammed M. S.; Bamaga, Ahmed K.; Alsubaie, Mohammed A.; Daghistani, Rawan; Baeesa, Saleh S.; et al. (Frontiers in Neurology, 2024)
Drug-resistant epilepsy (DRE) impacts a significant portion, one-third, of individuals diagnosed with epilepsy. In such cases, exploring non-pharmacological interventions are crucial, with the ketogenic diet (KD) standing out as a valuable option. KD, a high-fat and low-carb dietary approach with roots dating back to the 1920s for managing DRE, triggers the formation of ketone bodies and modifies biochemistry to aid in seizure control. Recent studies have increasingly supported the efficacy of KD in addressing DRE, showcasing positive outcomes. Furthermore, while more research is needed, limited data suggests that KD may also be beneficial for specific genetic epilepsy syndromes (GESs). This is a multi-center retrospective analysis of pediatric patients with GESs diagnosed using next-generation sequencing. The enrolled patients followed the keto-clinic protocol, and the KD efficacy was evaluated at 3, 6, and 12-month intervals based on seizure control and compliance. The collection instrument included demographic, baseline, and prognostic data. The collected data was coded and analyzed promptly. We enrolled a cohort of 77 patients with a mean current age of 7.94 ± 3.83 years. The mean age of seizure onset was 15.5 months. Notably, patients experienced seizures at a younger age tended to have less positive response to diet. Overall, 55 patients responded favorably to the diet (71.4%) while 22 patients (28.6%) showed no improvement. Patients with genetic etiology showed a significantly more favorable responses to the dietary intervention. Patients with Lennox-Gastaut syndrome showed the most significant improvement (14/15) followed by patients with Dravet syndrome (6/8), and West syndrome (3/4). The number of used anti-seizure medications also played a significant role in determining their response to the diet. While some patients experienced mild adverse events, the most common being constipation, these occurrences were not serious enough to necessitate discontinuation of the diet. The study revealed a high improvement rate in seizure control, especially among younger patients and those with later seizure onset. The success of dietary treatment hinges greatly on early intervention and the patient's age. Certain genetic mutations responded favorably to the KD, while efficacy varied among various genetic profiles.